2010
DOI: 10.1007/s00210-010-0529-2
|View full text |Cite
|
Sign up to set email alerts
|

Tissue functions mediated by β3-adrenoceptors—findings and challenges

Abstract: As β3-adrenoceptor agonists metamorphose from experimental tools into therapeutic drugs, it is vital to obtain a comprehensive picture of the cell and tissue functions mediated by this receptor subtype in humans. Human tissues with proven functions and/or a high expression of β3-adrenoceptors include the urinary bladder, the gall bladder, and other parts of the gastrointestinal tract. While several other β3-adrenoceptor functions have been proposed based on results obtained in animals, their relevance to human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 62 publications
0
26
0
Order By: Relevance
“…Studies on rat DSM have shown that BRL37744 also exhibit some antimuscarinic properties (5,26,30). In our study, we addressed this issue by using the muscarinic receptor antagonist atropine.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on rat DSM have shown that BRL37744 also exhibit some antimuscarinic properties (5,26,30). In our study, we addressed this issue by using the muscarinic receptor antagonist atropine.…”
Section: Discussionmentioning
confidence: 99%
“…The b 3 -adrenoceptor was originally assigned a role in promoting lipolysis and thermogenesis (Emorine et al, 1989;Arch, 2008), yet this function is most likely restricted to rodents (Michel et al, 2010). Multiple other roles for the b 3 -adrenoceptor were subsequently elucidated, including activation of nitric oxide synthase in cardiomyocytes, relaxation of the urinary bladder (Michel et al, 2010), and most recently release of hematopoietic stem cells and progenitor cells from the bone marrow in myocardial infarction (Dutta et al, 2012). The b 3 -subtype was the last of the b-adrenoceptors to Ahles and Engelhardt be cloned and has been studied considerably less compared with the b 1 -and the b 2 -subtype.…”
Section: Variants Of the B 3 -Adrenoceptormentioning
confidence: 99%
“…Therefore, most tissue mapping has relied on functional studies. Although this has provided robust evidence for a dominant role of the b 3 subtype in human bladder smooth muscle relaxation (Michel and Vrydag, 2006), the evidence for involvement of this subtype in the regulation of other tissues is less convincing due to a limited number of studies and poor selectivity of many of the tools used in those studies (Michel et al, 2010).…”
Section: Receptor Polymorphisms and Expression Patternmentioning
confidence: 99%